1983
DOI: 10.1002/ajpa.1330610104
|View full text |Cite
|
Sign up to set email alerts
|

True grit: A microwear experiment

Abstract: Recently we noted the effects of experimental diets on microscopic dental wear in the American opossum and concluded that it might prove difficult to distinguish the microwear produced by an insectivorous diet from that produced by some kinds of herbivorous ones. We also noted that wear caused by gritty diets and those containing plant opal, although they might be confused with one another, are easily distinguished from other sorts of dietary wear. Our conclusions have been challenged on the basis that possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 7 publications
(13 reference statements)
0
37
0
1
Order By: Relevance
“…Inadequate molds may have been primarily due to re-growth of the pellicle, the proteinaceous film produced from animal saliva that coats teeth. To improve success rate, a proteolytic enzyme treatment (Kay and Covert, 1983) can be applied to the occlusal surface after teeth cleaning, but before making the second mold. The molding plate should also be held in place, with the mouth held open, as we found that the anesthetized sheep were prone to moving their jaws and distorting the molds if their mouths were closed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inadequate molds may have been primarily due to re-growth of the pellicle, the proteinaceous film produced from animal saliva that coats teeth. To improve success rate, a proteolytic enzyme treatment (Kay and Covert, 1983) can be applied to the occlusal surface after teeth cleaning, but before making the second mold. The molding plate should also be held in place, with the mouth held open, as we found that the anesthetized sheep were prone to moving their jaws and distorting the molds if their mouths were closed.…”
Section: Discussionmentioning
confidence: 99%
“…Kay and Covert (1983) reported the complication of the pellicle, a proteinaceous film on teeth that can obscure dental impressions, in their live feeding trials with opossums. An enzyme can be applied to remove the pellicle; however, abrasives also obliterate the film.…”
Section: Feeding Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they added that species presenting high number of fine scratches occupy open areas as grasslands, where dust is abundant. Other studies also suggested that exogenous particles as dust, are also responsible for the large number of parallel striations, being not exclusively attributed to phytholiths alone (Gordon, 1982;Kay and Covert, 1983;Teaford, 1988;Ungar et al, 1995;Sanson et al, 2007). The dentition of the lineage Armantomys aragonensis-A.…”
Section: Paleoecological Analysesmentioning
confidence: 99%